2022
DOI: 10.1186/s12891-022-05675-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of open reduction of distal humerus fractures in children after implementation of an enhanced recovery after surgery program

Abstract: Objective This study assessed whether an enhanced recovery after surgery (ERAS) protocol could be beneficial for children with distal humerus fractures. Methods Children with distal humerus fractures (n = 85) were randomly assigned to the ERAS and control groups and subjected to different perioperative managements. This was followed by the evaluation of their intraoperative characteristics (operation time and bleeding), postoperative characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Surgeons, such as Henrik Kehlet [ 3 ], originally proposed the core concept of ERAS, which integrated multiple high-quality clinical evidence-based medical evidence into perioperative management to improve the perioperative trauma and stress response and accelerate recovery. A 2022 clinical study that applied the ERAS concept to 85 children undergoing surgery showed that the ERAS regimen could accelerate postoperative functional recovery without increasing the risk of postoperative nausea, vomiting, and poor incision healing; However, they mainly discussed pediatric orthopedics [ 4 ]. A team from the Hannover Medical School in Germany surveyed the length of stay, patient satisfaction, parent satisfaction, pain management, complications, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons, such as Henrik Kehlet [ 3 ], originally proposed the core concept of ERAS, which integrated multiple high-quality clinical evidence-based medical evidence into perioperative management to improve the perioperative trauma and stress response and accelerate recovery. A 2022 clinical study that applied the ERAS concept to 85 children undergoing surgery showed that the ERAS regimen could accelerate postoperative functional recovery without increasing the risk of postoperative nausea, vomiting, and poor incision healing; However, they mainly discussed pediatric orthopedics [ 4 ]. A team from the Hannover Medical School in Germany surveyed the length of stay, patient satisfaction, parent satisfaction, pain management, complications, etc.…”
Section: Discussionmentioning
confidence: 99%